2020
DOI: 10.3201/eid2606.190928
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Epidemiology of 2015–2016 Zika Virus Outbreak in Cape Verde

Abstract: Z ika virus (ZIKV), first discovered in Uganda in 1947 and sporadically found in Africa and Asia, was long believed to only cause mild disease in humans (1). ZIKV isolates are classified into 1 of 2 lineages, representing the African and Asian genotypes. ZIKVs of the African lineage have been isolated from many regions of Africa (2), mostly through entomologic investigations, and serologic evidence suggests that ZIKV infections in humans are frequent (3). However, until the 2000s, the virus had seldom been det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Genome sequencing of ZIKV strains. The consensus genome sequences of the seven ZIKV strains of the panel were obtained by high-throughput sequencing 24,92 . Briefly, RNA was extracted from virus stock using QIAamp Viral RNA Mini Kit (Qiagen) and treated with TURBO DNase (Ambion).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome sequencing of ZIKV strains. The consensus genome sequences of the seven ZIKV strains of the panel were obtained by high-throughput sequencing 24,92 . Briefly, RNA was extracted from virus stock using QIAamp Viral RNA Mini Kit (Qiagen) and treated with TURBO DNase (Ambion).…”
Section: Methodsmentioning
confidence: 99%
“…Autochthonous ZIKV transmission was also detected in Angola during the same time period with four confirmed acute Zika cases and several suspected cases of microcephaly. Phylogenetic analyses revealed that the ZIKV strains detected in Cape Verde and Angola belonged to the Asian lineage and were probably independently imported from Brazil 24 , 25 . So far, the African ZIKV lineage has never been detected outside the African continent and never been associated with epidemic transmission, birth defects or neurological disorders 9 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…aegypti population from Luanda, Angola consisted of a genetic mixture of Aaa and Aaf(6). Possibly, a similar situation could have facilitated the large ZIKV outbreak that occurred in Cape Verde during 2015-2016(42), based on the untested assumption that the local Ae. aegypti population there harbors a large proportion of 'domestic' ancestry similar to the nearby populations of Western Senegal.…”
mentioning
confidence: 99%
“…Briefly, RNA was extracted from virus stock using QIAamp Viral RNA Mini Kit (Qiagen) and treated with TURBO DNase (Ambion). The Senegal_2011 and Senegal_2015 strains also underwent depletion of host ribosomal RNA following a homemade protocol 25 . cDNA was produced with random hexameric primers (Roche) using M-MLV (Invitrogen) or Superscript IV (Thermo Fisher Scientific) reverse transcriptase.…”
Section: Genome Sequencing Of Zikv Strainsmentioning
confidence: 99%
“…Autochthonous ZIKV transmission was also detected in Angola during the same time period with four confirmed acute Zika cases and several suspected cases of microcephaly. Phylogenetic analyses revealed that the ZIKV strains detected in Cape Verde and Angola belonged to the Asian lineage and were probably independently imported from Brazil 25,26 . So far, the African ZIKV lineage has never been detected outside the African continent and never been associated with epidemic transmission, birth defects or neurological disorders 27 .…”
Section: Introductionmentioning
confidence: 99%